Antioxidant Protein Hydrolysates from Hemp Seed Oil Cake—Optimization of the Process Using Response Surface Methodology - Maria Doneva; Svetla Dyankova; Margarita Terziyska; Petya Metodieva; Iliana Nacheva (Applied Sciences, 2024)
Hemp seed oil cake, a by-product of hemp seed oil extraction, is characterized by its high protein content and bioactive components, making it a valuable resource for the development of functional products through enzymatic hydrolysis. Hemp seed oil itself is renowned for its rich content of essential fatty acids, vitamins, and antioxidants, contributing to its widespread use in health and wellness products. Consequently, the residual cake presents significant potential for the food, pharmaceutical, and cosmetic industries as a source of high-quality protein ingredients. The optimization of enzymatic hydrolysis conditions is crucial for maximizing the efficiency and quality of the resulting protein hydrolysates. This study aims to optimize the hydrolysis process of hemp seed oil cake with bromelain, focusing on three key factors: enzyme concentration (E/S ratio), temperature, and time, to achieve hydrolysates with superior antioxidant activity. Response Surface Methodology (RSM) was applied using a Box–Behnken design to model and optimize the hydrolysis conditions. The experimental design involved three levels for each factor: 1%, 2%, and 3% for bromelain concentration; 20 °C, 30 °C, and 40 °C for temperature; and 60, 120, and 180 min for hydrolysis duration, resulting in 21 experimental runs. The antioxidant activity was assessed via DPPH and ABTS radical scavenging assays (%RSA), and the derived regression models were statistically analyzed and validated. The findings indicate that the optimal conditions for obtaining protein hydrolysates with the highest antioxidant activity are a bromelain concentration of 3.0%, a temperature of 40 °C, and a hydrolysis time of 60 min.